Synchronous Reluctance Motor Performance Improvement Using MTPA Control Strategy and Five-Level Inverter Topology - Zahraoui, Yassine; Moutchou, Mohamed; Tayane, Souad; Fahassa, Chaymae; Elbadaoui, Sara; Ma'arif, Alfian (Journal of Robotics and Control (JRC), 2022)
An improved vector control method is presented in this study to enhance synchronous reluctance motor (SynRM) performance. The maximum torque per ampere (MTPA) technique has demonstrated good dynamic properties since the torque control is closely tied to the current control. The selection of the control approach is primarily influenced by how the reference current values will be defined. Additionally, a five-level neutral-point-clamped (NPC) inverter replaces the traditional two-level inverter. Only eight voltage vectors can be produced by a two-level inverter, whereas one hundred twenty-five voltage vectors can be generated by a five-level inverter. The goal is to produce an output voltage vector that closely resembles the reference voltage vector in order to ensure a quick response on the one hand and enhance dynamic performance on the other. An exact comparison of the suggested vector control strategy's properties is made once it has been simulated in MATLAB/Simulink. The acquired findings are satisfactory and high performance is attained in terms of response time, torque ripple reduction, and current waveform improvement.